Pushing the Limits: Chronotype and Time of Day Modulate Working Memory-Dependent Cerebral Activity - Schmidt, Christina; Collette, Fabienne; Reichert, Carolin F.; Maire, Micheline; Vandewalle, Gilles; Peigneux, Philippe; Cajochen, Christian (Frontiers in Neurology, 2015)
Morning type individuals experience more difficulties to maintain optimal attentional performance throughout a normal waking day than evening types. However, time-of-day modulations may differ across cognitive domains. Using functional magnetic resonance imaging (fMRI), we investigated how chronotype and time of day interact with working memory at different levels of cognitive load/complexity in a N-back paradigm (N0-, N2- and N3-back levels). Extreme morning and evening type individuals underwent 2 fMRI sessions during N-back performance, one 1.5 h (morning) and one 10.5 h (evening) after wake-up time scheduled according to their habitual sleep-wake preference. At the behavioural level, increasing working memory load resulted in lower accuracy, while chronotype and time of day only exerted a marginal impact on performance. Analyses of neuroimaging data disclosed an interaction between chronotype, time of day and the modulation of cerebral activity by working memory load in the thalamus and in the middle frontal cortex. In the subjective evening hours, evening types exhibited higher thalamic activity than morning types at the highest working memory load condition only (N3-back). Conversely, morning type individuals exhibited higher activity than evening type participants in the middle frontal gyrus during the morning session in the N3-back condition. Our data emphasize inter-individual differences in time-of-day preferences and underlying cerebral activity, which should be taken into account when investigating vigilance state effects in task-related brain activity. These results support the hypothesis that higher task complexity leads to a chronotype-dependent increase in thalamic and frontal brain activity, permitting stabilization of working memory performance across the day.